1996
DOI: 10.1093/chemse/21.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Recalling Taste Intensities in Sweetened and Salted Liquids

Abstract: The effect of training on recalling taste intensities over 6 weeks was studied using an ad libitum mixing procedure. Subjects tasted sweet and salty standards labeled as "weak' and "strong' (3 and 8% sucrose in redcurrant juice; 0.4 and 1.2% NaCl in beef broth). They subsequently mixed unsweetened and sweetened juice, and unsalted and salted broth, to produce taste intensities that corresponded to the standards. A minimum training (MT) group (n = 13) produced comparison stimuli by tasting and directly comparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…For texture judgements, Harker, Gunson, Brookfield, and White (2002) noted how judges were not accurate at comparing the hardness of apples eaten 1 min apart. Taste studies requiring judges to match taste intensities of previously tasted stimuli, by mixing strong and weak components, indicated a tendency to overestimate the intensity of stimuli tasted immediately beforehand (Theunissen, Tuorila, & Ahlströ m, 1993;Tuorila, Theunissen, & Ahlströ m, 1996;. For taste and odor stimuli, Barker and Weaver (1983) required judges to state whether a stimulus was greater, lesser or equal in intensity to stimuli tasted 1 min before; they found a tendency to underestimate the intensity of the previous stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…For texture judgements, Harker, Gunson, Brookfield, and White (2002) noted how judges were not accurate at comparing the hardness of apples eaten 1 min apart. Taste studies requiring judges to match taste intensities of previously tasted stimuli, by mixing strong and weak components, indicated a tendency to overestimate the intensity of stimuli tasted immediately beforehand (Theunissen, Tuorila, & Ahlströ m, 1993;Tuorila, Theunissen, & Ahlströ m, 1996;. For taste and odor stimuli, Barker and Weaver (1983) required judges to state whether a stimulus was greater, lesser or equal in intensity to stimuli tasted 1 min before; they found a tendency to underestimate the intensity of the previous stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Baker and Weaver (1983) found that the target taste stimuli were remembered as being weaker. On the other hand, it has been reported that the target taste stimuli was remembered as being stronger (Tuorila et al, 1996;Vanne et al, 1998). Such a difference in the directionality of change for taste memory might be due to differences in participants' first impressions of a taste during encoding.…”
Section: Implications For Past Taste/flavor Memory Studiesmentioning
confidence: 98%
“…In the past, studies of taste and flavor memory (Baker & Weaver, 1983;Tuorila et al, 1996;Vanne et al, 1998) used an intentional memory paradigm where participants consciously attempted to remember stimuli. However, in daily life many memories are of an incidental rather than intentional nature.…”
Section: Implications For Past Taste/flavor Memory Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We further observed a higher score on actual perceived cheese flavour than on remembered cheese flavour intensity (45 ± 2.4 versus 39 ± 2.4; p < 0.05), whereas saltiness remained the same (38 ± 2.3 versus 38 ± 2.4; p = 0.73). This might suggest that certain attributes gain or loose importance, while others remain invariable in consumer memory (see also Tuorila, Theunissen, & Ahlströ m, 1996).…”
Section: Introductionmentioning
confidence: 99%